2007
DOI: 10.4161/cbt.6.3.3704
|View full text |Cite
|
Sign up to set email alerts
|

Basic transcription factor 3 (BTF3) regulates transcription of tumor-associated genes in pancreatic cancer cells

Abstract: Basic transcription factor 3 (BTF3) acts as a transcription factor and modulator of apoptosis, and is differentially expressed in colorectal cancer and glioblastomas. In the present study, the expression of BTF3, as well as its role in apoptosis and gene transcription, was analyzed in pancreatic ductal adenocarcinoma (PDAC). QRT-PCR, immunohistochemistry, immunoblotting, and immunofluorescence analyses were carried out to investigate BTF3 mRNA/protein expression and localization. BTF3 silencing in pancreatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…It has been observed that down-regulation of BTF3a is involved in inhibition of transcription and proteins synthesis in the apoptotic K562 cells [33]. It also acts as a transcriptional regulator and is associated with apoptosis and/or cell cycle arrest [34], [35]. Two of the nucleic acid associated proteins involved in RNA processing were found to be significantly down regulated in case of the PR resistant strain.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that down-regulation of BTF3a is involved in inhibition of transcription and proteins synthesis in the apoptotic K562 cells [33]. It also acts as a transcriptional regulator and is associated with apoptosis and/or cell cycle arrest [34], [35]. Two of the nucleic acid associated proteins involved in RNA processing were found to be significantly down regulated in case of the PR resistant strain.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we focused our follow-up effort on BTF3 , since the relative expression of this gene in whole saliva was significantly associated with caries experience. BTF3 is involved in the initiation of transcription by RNA polymerase and is also involved in cell cycle regulation, apoptosis, and the transcriptional regulation of tumor-associated genes [Kusumawidjaja et al, 2007]. The protein encoded by CCNB1 is a regulatory protein involved in mitosis, and the gene product complexes with p34 (cdc2) protein kinase to form the maturation-promoting factor, which is required for cells to undergo mitosis [Brandeis et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…BTF3 has been found to be over expressed in cancer cells like sporadic colorectal cancer [31], glioblastoma multiforme [32] and pancreatic cancer cells [33], and it was argued that the down regulation of BTF3 gene in cancer cell may result in increased apoptosis of these cells, but this aspect is still under investigation. The confirmation of this fact will allow this peptide to be used as potential anti cancerous agent.…”
Section: Discussionmentioning
confidence: 99%